Agricultural land use modeling for grain crops in Diwaniyah district - Agricultural land use modeling for grain crops in Diwaniyah district; Researcher Karrar Hamza Rahyo (Journal of the College of Education for Girls for Humanities, 2023)
Abstract The research aims to modeling the use of agricultural land for grain crops in the detection of these uses on the farm level administrative units, knowledge of Cartographic modeling for this summer and winter crops, considering that the organization Cartographer at the heart of the geographical work, the emergence of GIS software revolutionized the spatial science in general, In geography in Particular, which led to a decline in the traditional ways in which researchers sought old to be found and developed to show other methods with minimal effort and a shorter time and more accuracy in the results. In this research Program use (Arc GIS.V.9.3) in conducting modeling uses farm land for grain crops operations in the district of Diwaniya, It was clear that this Program has the ability to build a cartographic models for grain crops and its variations at the level of administrative units in the study area, the brood search that interest in the cultivation of a large winter grain, especially wheat and barley crops, the lowest interest cultivation of summer crops for various reasons, including lack of water in the summer and the large spread of salinity in the soil and the lack of a lot of requirement that need summer grain unlike winter grains.